Protective effects of abdominal electroacupuncture on oxidative stress and inflammation due to testis torsion/detorsion in rats - Acioli,Porfirio Cezar Passos (2014)
PURPOSE:To evaluate the effects of acupuncture (Ac) and electroacupuncture (EAc) on oxidative stress and inflammation in testis torsion/detorsion (T/D) model in rats.METHODS: Thirty male Wistar rats were randomized into five groups. G1 Group (Sham) served as control. The remaining groups were submitted to spermatic cord torsion (720°) for 3 hours, followed by detorsion and reperfusion for 4 hours. Before detorsion G3, G4 and G5 rats were treated with Ac, EAc 2Hz and EAc 10 Hz, respectively, applied to acupoint Gulai (S-29) bilaterally under anesthesia for 5 minutes. Next, the testes were detorsioned and reperfused for 4 hours. Afterwards, blood samples and the right testis were collected for biochemical assays: reduced Glutathione (GSH), Malonaldehyde (MDA), Myeloperoxidase (MPO).RESULTS: EAc stimulation (2 and 10 Hz) promoted significant increase in concentrations of GSH in plasma and testis of G4-G5 rats, compared with G1. There was significant increase of tissue MDA in groups G4-G5 and plasma MDA in all groups, compared with G1. There was a significant reduction in MPO activity in groups G4-G5 compared with G1.CONCLUSION:Electroacupuncture stimulation (2 and 10 Hz) attenuates oxidative stress and inflammatory response in rats subjected to testicular torsion/detorsion.